An integrated multi-molecular sensor for simultaneous BRAFV600E protein and DNA single point mutation detection in circulating tumour cells. Issue 5 (9th January 2019) - Dey, Shuvashis; Koo, Kevin M.; Wang, Zhaoran; Sina, Abu A. I.; Wuethrich, Alain; Trau, Matt
Abstract : We report an integrated multi-molecular sensor (IMMS) platform for an entire sample-to-answer protocol encompassing melanoma cell capture in biological fluids, on-chip cell lysis, and combined quantification of intracellular BRAF V600E DNA and protein amounts. Abstract : The analysis of circulating cancer biomarkers in the form of liquid biopsies confers several potential benefits as compared to traditional surgical tissue sampling. As a common key anomaly strongly implicated across several cancer types, the BRAF V600E mutation is one of the most valuable oncogenic biomarkers available in liquid biopsies. Crucially, BRAF V600E is also an actionable mutation which could be arrested by clinically beneficial drug inhibitors. Yet, as is true for most single base disease mutations, current BRAF V600E detection in either its DNA or protein molecular state is still liable to false positive/negative outcomes, thus impacting patient treatment benefit. Here we present an integrated multi-molecular sensor (IMMS) for an entire sample-to-answer workflow from melanoma cell capture to simultaneous quantification of both intracellular BRAF V600E DNA and protein levels on a single platform. The IMMS combines (i) specific capture and release of circulating melanoma cells; (ii) electric field-induced cell lysis; (iii) simultaneous quantification of BRAF V600E DNA and protein levels. We investigated the IMMS system's analytical performance in cell capture, release and lysis, and intracellular BRAF V600E detection by ligase-mediated DNA amplification and antibody-based protein hybridization. As a proof-of-concept, we successfully demonstrated circulating BRAF V600E detection at both DNA and protein molecular levels in simulated melanoma plasma samples. With its capabilities in integrated and miniaturized analysis, the IMMS could lead the emergence of a new generation of multi-molecular lab-on-chip biosensors for enabling more accurate and extensive analysis of powerful circulating biomarkers in patient liquid biopsies.